SISTEM MONITORING SUHU DAN KELEMBAPAN INCUBATOR LABI-LABI BERBASIS IOT - Susanto, Andri; Sabah, Rafie Fazri (University of Muhammadiyah Tangerang, 2022)
Labi-labi or softshell turtles (Testudines; Trionychidae) is a group of freshwater turtles. Fisheries statistics have recorded freshwater turtles as one of the fishery commodities since the 1990s. In maintaining the labi population, cultivation is needed, a little bit of cultivation due to the small number of hatching manually, to facilitate cultivation, monitoring and monitoring data from time to time nominal value of the temperature and humidity of the hatchery incubator, an IoT-based turtle incubator temperature and humidity monitoring tool was made. This tool consists of ESP8266, MIST MAKER, LCD, RELAY, Fan, Power Supply, Smartphone, and 3 sensors, namely DHT11 sensor, SOIL MOISTURE sensor, DS18B20 sensor as a zone reading area from the sensor and then will be connected to the Blynk application. 3 sensors, will send input humidity and temperature data to ESP8266, from ESP8266 then the data will be processed and sent and displayed to the Blynk application via the internet network. From this tool, the largest error value is 0.6, and the largest standard deviation is 0.085, so that the data error rate or tolerance of 0.5494% is obtained. Keyword : Temperature and humidity, ESP8266, Soil Moisture, Blynk